Global campaign against epilepsy: assessment of a demonstration project in rural China - Wenzhi Wang; Jianzhong Wu; Xiuying Dai; Guangyu Ma; Bin Yang; Taiping Wang; Chenglin Yuan; Ding Ding; Zhen Hong; Patrick Kwan; Gail S Bell; Leonid L Prilipko; et al. (The World Health Organization, 2008)
OBJECTIVE: The Global Campaign Against Epilepsy demonstration project in rural China aimed: to reduce the treatment gap and morbidity of people with epilepsy by using community-level interventions; to train and educate health professionals; to dispel stigma; to identify potential for prevention and to develop models of integration of epilepsy control into the local health systems. We report the overall results of the demonstration project, focusing on the prevalence and the change in the treatment gap of epilepsy after an intervention. METHODS: Door-to-door epidemiological surveys were carried out before, and 6 months after the end of, an intervention project for epilepsy in rural settings in five provinces of China. The intervention consisted of a treatment programme available to patients without prior appropriate treatment and a public health educational programme about epilepsy. The sampled population in the second survey was 51 644 people. FINDINGS: In the second survey, epilepsy was confirmed in 320 people, yielding a lifetime prevalence of 6.2/1000 and a prevalence of active epilepsy of 4.5/1000. The lifetime prevalence and prevalence of active epilepsy in the first survey were 7.0/1000 and 4.6/1000, respectively. The treatment gap of active epilepsy in the second survey was 49.8%, 12.8 percentage points lower than that of the first survey (62.6%). CONCLUSION: The results of this study suggest that the intervention measures used were possibly effective and evidently feasible in rural China, contributing to a decrease in the treatment gap of epilepsy.